THE EFFECT OF OWN CAPITAL AND LOAN CAPITAL ON REMAINING OPERATING RESULTS IN COOPERATIVE VILLAGE UNIT (KUD) MANUNGGAL VILLAGE BANDAR PADANG SUBDISTRICT OF INDRAGIRI HULU DISTRICT - Walmi Sholihat (JURNAL MANAJEMEN DAN BISNIS, 2020)
This research was conducted at the Village Unit Cooperative (KUD) Manunggal Desa Bandar Padang Seberida District Indragiri Hulu Regency. The research carried out lasted for more or less 6 (six) months. The purpose of this study was to determine the effect of own capital and loan capital on the remaining operating results (SHU) in the Village Unit Cooperative (KUD) Manunggal Village Bandar Padang Seberida District Indragiri Hulu Regency. The study was conducted by quantitative methods, namely research that illustrates the influence of own capital and loan capital on the remaining operating results (SHU) in the Village Unit Cooperative (KUD) Manunggal Village Bandar Padang Seberida District Indragiri Hulu Regency. By analyzing data using multiple regression, correlation coefficients, and Hypothesis testing which will be assisted by using SPSS version 20. From the results of the study with the regression equation Y = 1,588,405 + 0,405 X1 + 0,122 X2.  a = constant of 1,588,405 means that the remaining operating results (SHU) (Y) is equal to 1,588,405  if (X1) (own capital) and (X2) (loan capital) equals 0 (zero). b1 = coefficient of own capital regression (X1) of 0.405 shows that each increase in equity (X1) of one unit and other variables (loan capital (X2)) remain, there will be an increase in remaining operating results (SHU) (Y) of 0.405 . b2 = loan capital regression coefficient (X2) of 0.122 indicates that for each increase in loan capital (X2) by one unit and another variable of own capital (X1) fixed, there will be an increase in the remaining operating result (SHU) (Y) of 0.122. The correlation coefficient is known that R is 0.544 which means it has a moderate and direct relationship. and then tested with the coefficient of multiple determination (R2) is 0.296. This shows that (X1) own capital and (X2) loan capital jointly can contribute to the variable (Y) remaining operating results (SHU) of 29.6%. And the remaining 70.4% is contributed by other variables. Hypothesis testing at a significant level = 5% where F table is 4.74. because F arithmetic (11,473)> F table (4.74) then Ho is rejected and Ha is accepted. This means that the variable capital alone and loan capital jointly have a significant influence on the remaining operating results (SHU) in the Village Unit Cooperative (KUD) Manunggal Village Bandar Padang Seberida District Indragiri Hulu Regency. Partial Test where t arithmetic (2.354)> than t table (2.306) then Ho is rejected and Ha is accepted, which means that equity itself has a significant effect on the remaining operating results (SHU). And t arithmetic (2.282)< than t table (2.306) then Ho is accepted and Ha is rejected, which means that loan capital does not have a significant effect on the remaining operating results (SHU).